Pengaruh Motivasi Ekstrinsik, Kompensasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan di Dinas Perhubungan Kabupaten Gunungkidul - Weningestri, Era; Septyarini, Epsilandri; Lysander, Mohammad Ahyar Syafwan (Universitas Batanghari Jambi, 2024)
The aim of this research is to find out how extrinsic motivation, compensation, and the working environment affect the job satisfaction of the staff of the Mountainkidul District Liaison Service. Using a purposeful selection strategy, 30 employees remain as samples of this research. The questionnaire was distributed to the permanent staff of the Mountainkidul District Liaison Service to be filled in for data collection purposes. The study includes the use of validity tests, reliability tests, conventional hypothesis tests, t tests, f tests, and determination coefficients tests. In data analysis, linear analysis is often used. According to research, extrinsic motivation has negative and insignificant influences, compensation has a positive and significant influence on employee job satisfaction, while the working environment has a negative and non-significant impact.